Galectin‐3 diminishes Wnt signaling in the postnatal subventricular zone. (8th June 2020) - Al‐Dalahmah, Osama; Nicholson, James; Draijer, Swip; Soares, Luana Campos; Szele, Francis G.
Abstract: Postnatal subventricular zone (pSVZ) stem and progenitor cell proliferation is regulated by several developmental signaling pathways such as Wnt/β‐catenin. However, the molecular regulation of Wnt function in the pSVZ is poorly understood. We previously showed that Wnt signaling is upregulated in an SVZ gliomagenesis in vivo model. As well, the pro‐inflammatory molecule Galectin‐3 (Gal‐3) increases Wnt signaling in cancer cells and is expressed in the SVZ. Therefore, we asked if Gal‐3 has a similar function on Wnt signaling in the pSVZ. We interrogated Wnt signaling using a signaling reporter as well as immunohistochemistry and showed that Wnt signaling predominates upstream in the pSVZ lineage but is downregulated in migrating neuroblasts. Biochemical analysis of SVZ cells, in vivo and in neurosphere stem/progenitor cells, showed that Gal‐3 physically interacts with multiple forms of β‐catenin, which is a major downstream regulator of Wnt signaling. Functional analyses demonstrated, in vitro and in vivo, that Gal‐3 knockdown increases Wnt signaling and conversely that Gal‐3 OE inhibits Wnt/β‐catenin signaling in the pSVZ. This latter result suggested that Gal‐3, which is consistently increased in brain injury, may decrease pSVZ proliferation. We showed that Gal‐3 OE decreased proliferation without altering cell cycle re‐entry and that it increased p27Kip1, a molecule which induces cell cycle exit. Our data uncover a novel regulator of Wnt signaling in the SVZ, Gal‐3, which does so in a manner opposite to cancer. Abstract : Decreased Galectin‐3 (Gal‐3) expression, by knockdown, increased Wnt/β‐catenin signaling whereas Gal‐3 overexpression decreased Wnt/β‐catenin signaling. We showed that Gal‐3 binds to β‐catenin. Concurrently, we found that Gal‐3 overexpression decreased proliferation and increased cell cycle exit.